Determination of Epoxy Groups on γ-Glycidoxypropyltrimethoxysilane Doped Nanosilicas by Oscillo-polarographic - Li, De-Liang; Zhang, Ling; Chang, Zhi-Xian; Zhang, Zhi-Jun (Asian Journal of Chemistry, 2010)
In the present work, oscillo-polarographic was developed to determine epoxy groups on γ- glycidoxypropyltrimethoxysilane (GPTMS) doped nanosilicas (GPTMS/nano-SiO2) quantitively. The method based on the quantitative reaction between dihydroxyl of hydrated epoxy groups and potassium periodate generating formaldehyde and the reaction between the formaldehyde and hydrazine sulfate generating a new compound (hydrazone) which could be adsorbed at the mercury electrode and yielded a sensitive polarographic wave. Optional conditions of sample treatment and ploargraphic determination were discussed in detail. This method involves simple operation and good accuracy for quantitive determination of epoxy groups on GPTMS/nano- SiO2. It also has the potential to provide information of the amount of epoxy groups on other similar category products.